Space-time processing for broadband wireless access. - Al-Dhahir, N.
We present an overview of research activities on space-time coding for broadband wireless transmission performed at AT&T Shannon Laboratory over the past two years. The emphasis is on physical layer modem algorithms such as channel estimation, equalization, and interference cancellation. However, we also discuss the impact of space-time coding gains at the physical layer on throughput at or above the networking layer. Furthermore, we describe a flexible graphical user interface attached to our physical layer simulation engine in order to explore the performance of space-time codes under a variety of practical transmission scenarios. Simulation results for the EDGE cellular system and the 802.11 wireless LAN environment are presented
Keywords: 802.11 wireless LAN environment; AT&T Shannon Laboratory; EDGE cellular system; Broadband wireless access; Channel estimation; Equalization; Graphical user interface; Interference cancellation; Networking layer; Physical layer; Physical layer modem algorithms; Physical layer simulation engine; Space-time coding; Space-time processing; Throughput